Penilaian Pengetahuan Bahasa Arab Berbasis Tes Subjektif Di MA Nurus Sunnah - Rohman, Saifur (Pascasarjana UIN Raden Mas Said Surakarta, 2021)
AbstractThis study aims to describe the process of assessing Arabic knowledge based on subjective tests at Madrasah Aliyah (MA) Nurus Sunnah. This study uses a qualitative descriptive method, where the researcher describes the data as it happens in the field. The data collection techniques used are in the form of direct observation in the field, documentation, and interviews. The results show that the knowledge assessment process using subjective tests at MA Nurus Sunnah has not fully met the ideal assessment criteria, with details: a) Basic competencies and subject indicators have been checked. b) The purpose of the assessment has been determined. c) There is no question grid. d) Scoring guidelines are not written neatly, and only in the form of personal notes. e) Questions are analyzed qualitatively.Keywords: knowledge assessment, subjective test, Arabic.